(NgRAFINQ {ARNI(B: [(NrOMAN(B] / s (N~ASTX (B1s - (Nd@MA(B, (NaLEKSANDRs ((NtA[KENT(B: s (NiZDATELXSKO(B-(NPOLIGRAFI^ESKOE OB_EDINENIE IMENI gAFURA gULQMA(B, s, 1993)
(NiSTORIKO(B-(NPRIKL@^EN^ESKIJ ROMAN a(B. (Nd@MA (B"(NgRAFINQ {ARNI(B" (NPOWESTWUET OB \POHE l@DOWIKA (BXVI.s
rus
Keywords: (NiSTORI^ESKIJ ROMANs; (NpRIKL@^EN^ESKIJ ROMANs